Synthesis of an Acrylamide Copolymer Containing Nano-SiO2 by Ex Situ Cu(0)-Mediated SET-LRP - Ling Wang; Zhendong Li; Pingsen Huang; Wei Ding (International Journal of Polymer Science)
We report herein the synthesis of a novel star-shaped copolymer containing nano-SiO2 by single-electron transfer living radical polymerization (SET-LRP) in aqueous solution. The effects of polymerization conditions, such as the total amounts and molar ratios of the monomer, initiator, catalyst, ligand, and modified nano-SiO2, have been investigated through a series of experiments. The prepared acrylamide copolymers have been characterized by FTIR spectroscopy and 1H NMR spectrometry. The properties of the copolymers have been assessed by viscometry and rheometry. The results confirmed that the nano-SiO2 functional monomer was successfully combined in the SET-LRP. The optimum polymerization conditions were established through orthogonal experiments as a ratio of [AM] : [DMAEMA] : [I] : [CuBr] : [Me6TREN] of 674.4 : 35.5 : 1 : 1 : 2 at a total concentration of [AM] + [DMAEMA] of 2.5 mol/L. The appropriate concentration of the nano-SiO2 functional monomer (NSFM) was 0.5 wt% with respect to AM + DMAEMA. The rheology of the star-shaped copolymer exhibited a shear-thickening property when the shear rate exceeded a critical value (100 s−1). The AM/DMAEMA/NSFM copolymer displayed a higher viscosity than AM/DMAEMA at the same concentration. It was found that AM/DMAEMA/NSFM exhibited better salt and temperature tolerances.